99 ESOPHAGECTOMY FOR THE PATIENTS WITH SQUAMOUS CELL CARCINOMA OF THE ESOPHAGUS AFTER ALLOGENEIC HEMATOPOIETIC STEM CELL TRANSPLANTATION. (17th September 2021) - Kato, Fumihiko; Daiko, Hiroyuki; Kanamori, Jun; Inamoto, Yoshihiro; Fukuda, Takahiro; Hayashi, Koji; Tachimori, Yuji; Koyanagi, Kazuo
Abstract:  : The number of long-term survivors after allogeneic hematopoietic stem cell transplantation (HSCT) has increased recently. Esophageal squamous cell carcinoma occurs at a particularly high incidence as a secondary cancer after HSCT. However, standard treatment for these patients has not been established yet. The objectives of this study were to investigate outcomes of esophagectomy for esophageal carcinoma developed in HSCT patients, and to provide the appropriate perioperative management. Methods: Ten HSCT patients underwent esophagectomy for esophageal squamous cell carcinoma between December 2007 and September 2017. The surgical outcomes and long-term prognosis of these patients were reviewed retrospectively. Results: In the former group, 5 of the 7 patients (71.4%) developed pneumonia after esophagectomy, with two of them requiring intubation because of respiratory failure. None of the three patients of the latter group, who received broad-spectrum antibiotics for more than 7 days after the surgery, developed any postoperative complications. The estimated survival probability of these patients at 5 years after the surgery was 53.3%. Conclusion: HSCT patients have an extremely high risk of developing pneumonia after esophagectomy, and the condition can easily become serious. Therefore, broad-spectrum antibiotics should be administered prophylactically to prevent severe pneumonia during the perioperative period in these patients.